Nutrient management in bitter gourd under partial shade - Ravikrishnan MK (Department of Agronomy, College of Agriculture, 1989)
A field experiment was conducted at the College of Agriculture, Vellayani during 1988 to study the influence of three levels of each nitrogen (50, 70 and 90 kg/ha), phosphorus (15, 25 and 35 kg/ha) and potassium (25, 50 and 75 kg /ha) on growth, yield, content and uptake of major nutrients in bittergourd VK-1 (Priya) under partially shaded conditions of coconut gardens. The trial was conducted as 33 + 1 partially confounded factorial experiment in Randomised Block design with two replications. Higher levels of nitrogen had profound influence on growth characters like days for opening of first male and female flowers and their node of emergence, internodal length, length of main vine and total dry matter production. Application of phosphorus of 35 kg/ha had significant positive effect on the node of emergence of first female flower and total dry matter production. Yield attributes like sex ratio, fruits per plant and harvest index were not influenced significantly by the main and interaction effects of the major nutrients. However the control plots registered a significant reduction in values for these parameters. The fruit set was maximum at 90 kg/ha of nitrogen, 25 kg/ha of phosphorus and 25 kg/ha of potash. Application of 90 kg N/ha, 25 kg P2O5/ha and 50 kg K2O/ha recorded the maximum yield. The response of bittergourd to nitrogen levels was linear and that to phosphorus levels was quadratic. Application of potassium at 75 kg K2O/ha was found to significantly increase the fruit weight. The length and girth of the fruits were positively influenced by the application of nitrogenous fertilizer. Potassium at the rate of 75 kg K2O/ha recorded the maximum girth of fruits signifying its effect on this character. The nitrogen and phosphorus content of fruits and plants and protein content of fruits were found to be unaffected by the main effects of nitrogen, phosphorus and potash. An increase in potash level increased the potassium content of fruits and plants. Nitrogen at 90 kg/ha significantly increased the nitrogen uptake by plants and fruits and phosphorus uptake by plants as compared to other levels. Maximum potassium uptake by fruits was obtained by application of 35 kg P2O5/ha and 75 kg K2O/ha and uptake of potassium by plants was maximum at 90 kg N/ha, 35 kg P2O5/ha and 75 kg K2O/ha. The study indicated that application of 90 kg N/ha 25 kg P2O5/ha and 50 kg K2O/ha recorded the maximum yield and net returns from bittergourd cv. VK-1 (Priya) under partially shaded conditions of coconut gardens in the red loam soils of Vellayani.